Just Do It? The Adoption of Sustainable Supply Chain Management Programs from a Supplier Perspective (2014)
Although many multinational companies are engaged in formal sustainability programs in order to upgrade social and environmental conditions within their supply chains, little is known about adoption at the supplier’s level. Using neo-institutional theory and building on an indepth case study of a middle-sized supplier of a multinational company in the food industry in Latin America, we explore how the firm integrates the requirements of a supplier development scheme and to what extent these demands are diffused to next-tier suppliers. Beyond coercive pressures, our results reveal the role of embedding sustainability demands into local network ties to foster adoption and diffusion in the upstream chain.